A fucoidan from Sargassum fusiforme with novel structure and its regulatory effects on intestinal microbiota in high-fat diet-fed mice. (1st October 2021) - Liu, Xue; Xi, Xiangyu; Jia, Airong; Zhang, Miansong; Cui, Tingting; Bai, Xinfeng; Shi, Yaping; Liu, Changheng
Highlights: The fucoidan SFP was mainly constituted by fucose and galactose. SFP mainly consisted of 1, 3-, 1, 4-, 1, 3, 4-linked-α-l -Fuc p and 1, 3-, 1, 6-linked-β-d -Gal p, partially sulfated at C-4, C-3, C-6 of the sugar residues. The branches were composed of sulfated fucosyl and galactofucosyl oligosaccharides. SFP had certain regulatory effect on intestinal flora disorder in high-fat diet-fed mice. Abstract: A fucoidan SFP, having novel structure, was extracted from Sargassum fusiforme . It had a molecular weight of 703 kDa and was composed of fucose and galactose with the ratio of 73.16:26.84 (mol%). Structural analyses showed that it mainly consisted of 1, 3-, 1, 4-, 1, 3, 4-linked-α-l -Fuc p and 1, 3-, 1, 6-linked-β-d -Gal p, with partial sulfation at C-4, C-3 of fucose units and C-6, C-3 of galactose units. The branches consisted of sulfated fucosyl and galactofucosyl oligosaccharides. The regulatory effects of SFP on the intestinal microbiota in high-fat diet-fed mice were investigated. The high-dosage SFP exhibited good hypolipidemic effects, especially in regulating the high-density lipoprotein cholesterol, non-esterified fatty acid levels and lipase activity. It also significantly decreased the ratio of phyla Firmicutes/Bacteroidetes ( P < 0.05). Besides, SFP had certain effects on the richness and diversity of intestinal microbiota. Therefore, SFP exhibited novel structure and certain beneficial effects on the disorder of intestinal microbiota in high-fat diet-fed mice.